EKSPLORASI ISU ETIKA DAN SOSIAL DALAM IMPLEMENTASI POLISI ROBOT OTONOM UNTUK PENEGAKAN HUKUM DI INDONESIA - Al Adawiah, Rabiah; Rabiah Al Adawiah; Nina Zainab (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2026)
The implementation of Autonomous Robot Police (e.g., i-K9 and humanoid robots) by the Indonesian National Police (Polri) marks a new era of smart policing. This research aims to critically explore the pressing ethical and social issues arising from the automation of law enforcement in the Indonesian context. Through a qualitative approach and conceptual analysis, the study identifies three main issue clusters: (1) Ethics of Accountability, focusing on the dilemma of criminal liability when autonomous robots make mistakes; (2) Social Issues of Public Trust, examining how AI surveillance affects the police's sense of security and legitimacy; and (3) Algorithmic Bias, emphasizing the potential for discrimination hidden in training data. It finds that despite offering operational efficiency, Autonomous Robot Police raises serious normative uncertainties, particularly regarding the transparency of decisions and the protection of public privacy under the Electronic Information and Transactions Law (UU ITE). Key recommendations include the establishment of comprehensive regulations, human resource training, and the development of AI governance that prioritizes the values ​​of social justice